2008
DOI: 10.1021/ja7113213
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Dendritic Effect in Multivalent Enzyme-Like Catalysts

Abstract: Functionalization of multivalent structures such as dendrimers and monolayer passivated nanoparticles with catalytically active groups results in very potent catalysts, a phenomenon described as the positive dendritic effect. Here, we describe a series of peptide dendrons and dendrimers of increasing generation functionalized at the periphery with triazacyclononane, a ligand able to form a strong complex with Zn(II). Kinetic studies show that these metallodendrimers very efficiently catalyze the cleavage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 66 publications
(134 reference statements)
0
44
0
Order By: Relevance
“…To have a meaningful discussion of these “averaged” values, one has to know the intrinsic effect originating from the multivalency of the system. Previously we have performed such an analysis on a series of homofunctionalised dendrimers of increasing valency 42. Rather interestingly, we observed that the clustering of catalytic units on a multivalent scaffold gives spontaneously rise to a positive dendritic effect; that is, an increased catalytic efficiency ( k cat / K M ) as a function of the dendrimer valency on the condition that catalysis requires the simultaneous action of two catalytic units.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To have a meaningful discussion of these “averaged” values, one has to know the intrinsic effect originating from the multivalency of the system. Previously we have performed such an analysis on a series of homofunctionalised dendrimers of increasing valency 42. Rather interestingly, we observed that the clustering of catalytic units on a multivalent scaffold gives spontaneously rise to a positive dendritic effect; that is, an increased catalytic efficiency ( k cat / K M ) as a function of the dendrimer valency on the condition that catalysis requires the simultaneous action of two catalytic units.…”
Section: Resultsmentioning
confidence: 93%
“…In all cases we have shown that catalysis requires the cooperative action of two catalytic units. For systems 3 42 and 4 ,59 we were able to determine the Michaelis–Menten parameters, which are added in Table 2. By themselves these are reasonable catalysts in terms of rate acceleration ( k cat / k uncat ), but their activity becomes insignificant when compared to the NP‐based system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These catalysts take advantage of the "dendritic effect", which does not necessarily mimic the specific microenvironment characteristic of an enzymatic pocket, but allows the formation of catalytic sites in which multiple catalytic units act A C H T U N G T R E N N U N G cooperatively on the substrate. [35] It is not clear, a priory, which polymer modifications create the right sort of environment, so we again use protocols for the combinatorial modification of PEI. These allow the incorporation of hydrophobic groups (mimicking the "hydrophobic core" of an enzyme) and guanidinium groups in varying proportions (reflecting the natural phosphate anchor arginine that is frequently found in active sites).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed kinetic studies revealed that catalysis results from the cooperative action of two triazacyclononane·Zn II (TACN·Zn II ) complexes localized on the surface of the monolayer. [21,22] Au-MPC 1, which is fully covered with the TACN·Zn II complex, displays enzymelike saturation behavior with the "overall" values k cat = 6.7 10 À3 s À1 and K M = 0.31 mm at pH 7.5 in H 2 O. [23] This system is intriguing for the following reasons: a) under the experimental conditions, there is practically no background reaction, since k uncat under the same conditions is of the order of 10 À7 s À1 ; b) the reaction can be monitored visibly by measuring the absorbance of the p-nitrophenol product at 400 nm; c) a surprisingly high affinity is observed for the binding of HPNPP to 1.…”
mentioning
confidence: 99%